Designing decentralized food security and nutrition policies: a knowledge-based system approach in Malawi - Babu, Suresh Chandra (International Food Policy Research Institute, 1997)
Designing decentralized policies has been recently recognized as more appropriate to address the immediate development problems of local communities. In this paper, a knowledge-based system approach is used to generate decentralized policy recommendations of crop choices in order to achieve household food security and nutrition. Using a case study of smallholder Malawian farmers, a decentralized approach to production-oriented policymaking for household food security and nutrition is presented. Based on solutions of farm level optimization models and with the facilities of macro-programming in spreadsheet programs a rule-based system which is easily understood and modified by the local development agents with little or no knowledge of programming languages is developed. It is argued that similar programs could be written for designing and implementing decentralized policies for other rural development sectors. Given the increased use of microcomputers at district and sub-regional levels in sub-Saharan Africa, the approach developed in this paper could be highly practical in designing decentralized food and nutrition policies where experts in these fields are scarce.